Extraction and Characterization of Nanocrystalline Cellulose from Sugar Palm Fibres (Arenga Pinnata) - Ritonga, Sally Irvina; Frida, Erna; Humaidi, Syahrul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
In this work, cellulose was isolated from sugar palm fibre (Arenga pinnata) and converted into sugar palm fibre nanocrystalline cellulose (NCCs) in the hamlet of Medan Sinembah, Indonesia. Alkalization and bleaching were the stages of the therapy process. The cellulose removed with 30 weight percent concentrated sulfuric acid was then used to isolate NCC. Using Fourier transform infrared spectroscopy (FT-IR), the chemical make-up of sugar palm fibre and NCCs was identified. On the basis of structural analysis, X-ray diffraction (XRD) was used. Scanning electron microscopy (SEM) was used for morphological examination, while transmission electron microscopy (TEM) was used to look into NCCs. The outcomes demonstrated that the extracted cellulose underwent bleaching and alkalization processes, respectively, to eliminate lignin and hemicellulose. The diameters of the sugar palm fibre and NCCs were determined 69.025 Âµm to 6.07Â±0.14 nm and, respectively